2016
DOI: 10.1002/fuce.201500032
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Temperature and Composition on the Operation of Al Anodes for Aluminum‐Air Batteries

Abstract: The influence of composition and temperature on the anode polarization and corrosion rate of pure Al and Al‐In anodic alloys in 8M NaON electrolyte has been investigated. High current density (more than 800 mA cm−2) and faradaic efficiency over 97% were observed for all investigated alloys at 60 °C. Lower temperature provides lower current density (200–300 mA cm−2 at 40 °C, and less than 100 mA cm−2 at 25 °C). Different formation of the product reaction layers was observed for pure aluminum and Al–0.41In alloy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In working AAB such temperature of electrolyte can be maintained due to the heat released during its operation [3]. However when AAB remains for a long time in standby mode at low ambient temperatures the problem of its quick self-heating to operating temperatures, for instance, by operating in short circuit mode, is arising.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In working AAB such temperature of electrolyte can be maintained due to the heat released during its operation [3]. However when AAB remains for a long time in standby mode at low ambient temperatures the problem of its quick self-heating to operating temperatures, for instance, by operating in short circuit mode, is arising.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of alkaline electrolyte composition and temperature on aluminum anode polarization and performance of aluminum-air cell with forced electrolyte circulation at heightened temperatures was investigated in detail in [2,3]. When concerning design of portable AABs, the results obtained in [4,5] are useful.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are a few reports on bifunctional catalysts for Mg–air batteries in the past two years . Meanwhile, aluminum–/iron–air batteries are under the similar condition . Thus, it is extremely important to develop new bifunctional catalysts for high‐performance rechargeable Mg–air, Al–air, and Fe–air batteries.…”
Section: Othersmentioning
confidence: 99%
“…10 Egan DR considered that 60°C is the optimum ambient condition for aluminum air-battery system and studied the electrochemical characteristics of aluminum air-battery anode at 60°C. 22 Ilyukhina AV used 8-M NaOH as the electrolyte of the aluminum air battery, and the OCV of the aluminum air battery measured at 60°C is 1.934 V. 23 Adhikari S studied the change of the anode potential when the aluminum plate was dissolved at 21°C to 22°C and found that the initial potential change was caused by the reaction of the Al 2 O 3 on the aluminum plate in the electrolyte and the second stage was caused by impurities such as copper and iron enriched on the surface of the aluminum plate, which accelerate the polarization process of the negative electrode. 24 Jingling Ma adopted aluminum alloy with unique elements as the negative electrode material, and KOH, NaOH, and NaCl were selected as electrolyte, respectively.…”
Section: Introductionmentioning
confidence: 99%